Mental Attitudes of Geriatric Edentulous Patients: A Review - Bhochhibhoya, Amar (Journal of Nepalese Prosthodontic Society, 2019)
Caring for the geriatric edentulous patients is challenging, as it requires a holistic approach, which addresses both the physical as well as the psychological aspects of such patients. Considering the increase in number of elderly individuals, the clinician should have adequate patience and understanding of psychological and emotional factors to tactfully deal with their problems. The appraisal of psychology and mental attitude for the overall success of complete denture rehabilitation is well recognized. Although important, these aspects are ignored occasionally, which is one of the major reasons for the failure of adequately constructed complete dentures. This article provides a comprehensive review of relevant literature on the mental attitudes and personality of geriatric patients and highlights the necessity of considering these factors for the overall success of complete denture treatment.